Determinants of health-related quality of life after out-of-hospital cardiac arrest (OHCA): a systematic review - Pek, Pin Pin (2023)
Objective: With a growing number of out-of-hospital cardiac arrest (OHCA) survivors globally, the focus of OHCA management has now broadened to survivorship. An outcome central to survivorship is health-related quality of life (HRQoL). This systematic review aimed to synthesise evidence related to the determinants of HRQoL of OHCA survivors. Methods: We systematically searched MEDLINE, Embase, and Scopus from inception to 15 August 2022 to identify studies investigating the association of at least one determinant and HRQoL in adult OHCA survivors. All articles were independently reviewed by two investigators. We abstracted data pertaining to determinants and classified them using a well-established HRQoL theoretical framework – the Wilson and Cleary (revised) model. Results: 31 articles assessing a total of 35 determinants were included. Determinants were classified into the five domains in the HRQoL model. 26 studies assessed determinants related to individual characteristics (n = 3), 12 studied biological function (n = 7), nine studied symptoms (n = 3), 16 studied functioning (n = 5), and 35 studied characteristics of the environment (n = 17). In studies that included multivariable analyses, most reported that individual characteristics (older age, female sex), symptoms (anxiety, depression), and functioning (impaired neurocognitive function) were significantly associated with poorer HRQoL. Conclusions: Individual characteristics, symptoms, and functioning played significant roles in explaining the variability in HRQoL. Significant nonmodifiable determinants such as age and sex could be used to identify populations at risk of poorer HRQoL, while significant modifiable determinants such as psychological health and neurocognitive functioning could serve as targets for post-discharge screening and rehabilitation plans. PROSPERO registration number: CRD42022359303.